Identidade adventista em questão: construção, transmissão e tendências polarizantes que desafiam a sua preservação na condição pós-moderna - Santos, Eduardo Cavalcante Oliveira (2021)
The present work entitled, Adventist Identity in question: construction, transmission and polarizing trends that challenge its preservation in the postmodern condition, contemplates the analysis of the polarizing trends that challenge the preservation of the Adventist identity in the postmodern condition, with the objective of evaluating the maintenance and integrity of the Adventist identity in post-modernity. Due to a growing concern on the part of leaders and theologians of the denomination with the politicalreligious polarization in Adventism, this research seeks to elucidate the questions that surround the Adventism and postmodernity problem. This religious polarization would also be a product of the political polarization that was accentuated after the campaign and the result of the 2018 Brazilian presidential changes. This clash has strong expression in social networks and mainly affects young people and their young or adult influencers, often outsiders to dialogue and eager for mutual aggression. Almost a century and a half passed after the arrival of the first Adventist magazines and missionaries in Brazil, and in that period the world and society changed. With this, groups emerged seeking an update on the “way” of being an Adventist and, on the other hand, there was a reaction from those who intend that nothing needs or should be changed. Hence the main question, which we intend to answer: What are the polarizing challenges arising from the post-modern condition that put at risk the preservation of the identity of the Seventh-day Adventist Church